VARIABEL MAKRO EKONOMI DALAM MEMPENGARUHI PERKEMBANGAN SAHAM SYARIAH DI JAKARTA ISLAMIC INDEX (JII) PERIODE 2013-2017 - Budi Gautama Siregar; Muhammad Isa (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2020)
The stock price is one factor for investors in making decisions. The decline in the performance of the JII index was caused by several factors such as Indonesia's macroeconomic sentiment and plans to withdraw monetary stimulus funds by the US central bank. This study aims to analyze the effect of inflation, interest rates and exchange rates on the development of Islamic stock prices in JII. This type of research is associative, using purposive sampling technique, the number of companies is 9 for a period of 5 years. Research data processing is carried out with the help of SPSS 22. Partial research results show that inflation has a significant effect on the development of stock prices, interest rates have a significant effect on price development and the exchange rate (exchange rate) has a significant effect on the development of stock prices. While simultaneous inflation, interest rates and exchange rates significantly influence the development of stock prices. R Square test in this study amounted to 0.224 means that the variable development of stock prices can be explained by inflation, interest rates and exchange rates 22.4 percent while the remaining 77.6 percent can be explained by other variables not included in this study.